Increased circulating serpinB1 levels in children with overweight/obesity are associated with obesity-related parameters: a cross‑sectional study - Qing Li; Zhuxi Li; Shusen Guo; Sujuan Li; Minglan Yao; Yingying Li; Xiaoping Luo (BMC Pediatrics, 2024)
Abstract Background Circulating serpinB1 levels are increased in obese mice and have been shown to promote β-cell proliferation in several species. However, the data on serum serpinB1 levels in children with obesity are scarce. This study aimed to determine serum serpinB1 levels in children with overweight/obesity, and to study its association with obesity-related parameters. Methods A total of 54 children with overweight/obesity and 36 normal-weight healthy controls aged 6–14 were recruited in this study. Anthropometric parameters, glucolipid metabolic biochemical parameters, sex hormones, and serum serpinB1 levels were measured in all subjects. The association of serum serpinB1 levels with obesity-related parameters and the risk of overweight/obesity were analyzed using correlation analysis and binary regression analysis, respectively. Results The serum serpinB1 level in overweight/obese children was notably greater than in normal-weight controls (2.03 ± 0.70 vs. 1.41 ± 0.58 ng/mL, p < 0.001). SerpinB1 levels were positively correlated with body mass index (BMI), BMI Z-score, triglyceride (TG), uric acid, fasting insulin, C-peptide, and homeostasis model assessment of insulin resistance (HOMA-IR) levels. Additionally, we found that elevated circulating serpinB1 levels were associated with the increased risk of childhood overweight/obesity even after adjustment for age, gender, and HOMA-IR (odds ratio, 4.132; 95% confidence interval, 1.315–12.983; p = 0.015). Conclusions Circulating serpinB1 level was significantly increased in children with overweight/obesity and positively associated with obesity-related glucolipid metabolic parameters. These results indicate a close association between serum serpinB1 concentrations and childhood overweight/obesity.